2024
DOI: 10.1002/ctm2.1572
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic alterations of peripheral blood immune cells and heterogeneity of neutrophil in intracranial aneurysms patients

Xiaolong Ya,
Long Ma,
Chenglong Liu
et al.

Abstract: BackgroundIntracranial aneurysms (IAs) represent a severe cerebrovascular disease that can potentially lead to subarachnoid haemorrhage. Previous studies have demonstrated the involvement of peripheral immune cells in the formation and progression of IAs. Nevertheless, the impact of metabolic alterations in peripheral immune cells and changes in neutrophil heterogeneity on the occurrence and progression of IAs remains uncertain.MethodsSingle‐cell Cytometry by Time‐of‐Flight (CyTOF) technology was employed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“… 8 Previous high‐dimensional analyses have found abnormal activation and functional dysfunction of various PBMC subsets in the peripheral blood of patients with IAs. 9 , 10 Studies suggested that the behavior and function of immune cells in immune responses were mainly regulated by their own metabolic patterns. 11 , 12 Abnormal activation and functional changes are closely related to specific metabolic shifts.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Previous high‐dimensional analyses have found abnormal activation and functional dysfunction of various PBMC subsets in the peripheral blood of patients with IAs. 9 , 10 Studies suggested that the behavior and function of immune cells in immune responses were mainly regulated by their own metabolic patterns. 11 , 12 Abnormal activation and functional changes are closely related to specific metabolic shifts.…”
Section: Introductionmentioning
confidence: 99%